A study of a PERMA-based positive psychological intervention programme in subthreshold depressed patients with newly diagnosed breast cancer: formulation and application - Wang, Deju; Li, Bin; Xin, Hongmei; Wu, Xiaofei; Xia, Jieqiong (Frontiers in Psychology, 2024)
Background Depression seriously affects the quality of life of breast cancer patients and even hinders treatment and recovery after diagnosis. Subthreshold depression should be worthy of attention, and the risk of subthreshold depression developing into depression increases if timely intervention is not available. However, there is limited research on interventions for subthreshold depression, especially for newly diagnosed breast cancer patients. Objective Exploring the efficacy of a PERMA-based positive psychological intervention programme in newly diagnosed breast cancer patients with subthreshold depression. Methods Using PERMA as a framework, we constructed the intervention programme through a literature review and expert discussion approach, and revised the programme using the Delphi method. Then we selected 84 newly diagnosed breast cancer patients for a randomised controlled trial. The control group received conventional care (primary care, specialist care, psychological care, etc.), and the observation group received a PERMA-based positive psychological intervention programme. Patient data were collected before and after the intervention, and the dataset consisted of patient responses to general information, the Depression Screening Scale (CES-D), the Hamilton Depression Inventory (HAMD-17), and the Questionnaire on Psychosocial Adjustment in Breast Cancer Patients. Results A total of 79 patients completed the study (38 patients in the observation group and 41 patients in the control group), and before the intervention, there were no statistical differences in the comparison of general information, subthreshold depression scores, and psychosocial adaptation scores between the two groups (p > 0.05). After the intervention, the subthreshold depression (CES-D and HAMD-17 scores) scores of the observation group were lower than those of the control group (p < 0.01), and the psychosocial adaptation scores were significantly higher than those of the control group (p < 0.01). Conclusion A positive psychological intervention programme using PERMA as a framework was more effective in reducing subthreshold depression levels and promoting levels of psychosocial adjustment in newly diagnosed breast cancer patients. Implications for practice Interventions for subthreshold depression are not limited to the traditional aftercare model, but rather from a positive psychology perspective. Especially for patients newly diagnosed with breast cancer, this is a new endeavour that has important implications for them. Because, instead of focusing on their negative emotions, we help them gradually adapt to their new identity and treatment process from a positive aspect during their most difficult period, thus reducing their subthreshold depression level and preventing it from developing into a more severe depression.